2016
DOI: 10.1002/hep.28373
|View full text |Cite
|
Sign up to set email alerts
|

Cholestasis‐induced adaptive remodeling of interlobular bile ducts

Abstract: Cholestasis is a common complication in liver diseases that triggers a proliferative response of the biliary tree. Bile duct ligation (BDL) is a frequently used model of cholestasis in rodents. To determine which changes occur in the three‐dimensional (3D) architecture of the interlobular bile duct during cholestasis, we used 3D confocal imaging, surface reconstructions, and automated image quantification covering a period up to 28 days after BDL. We show a highly reproducible sequence of interlobular duct rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
109
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 24 publications
2
109
1
2
Order By: Relevance
“…S10). Our results confirm earlier data showing that in response to different injuries the plasticity of the biliary tree is remodelled accordingly2021, and suggest that the use of IFX and DEX may have an unprecedented impact on the flexibility of this hepatobiliary system. Contrarily to CDE, in DDC settings the remodeling of the biliary architecture was obvious and was therefore not quantified.…”
Section: Resultssupporting
confidence: 91%
“…S10). Our results confirm earlier data showing that in response to different injuries the plasticity of the biliary tree is remodelled accordingly2021, and suggest that the use of IFX and DEX may have an unprecedented impact on the flexibility of this hepatobiliary system. Contrarily to CDE, in DDC settings the remodeling of the biliary architecture was obvious and was therefore not quantified.…”
Section: Resultssupporting
confidence: 91%
“…A limitation of the experimental validation presented here is that the analysis of images was performed in a two-dimensional manner. In the past, we have reported that threedimensional structures can easily be misinterpreted when only two-dimensional tissue slices are evaluated (Vartak et al 2016;Drasdo et al 2014a, b). For example, a column of initiated cells may appear as a single cell when the slice level is oriented perpendicular to the structure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, techniques of spatio-temporal tissue modeling have been established that allow simulations of how specific biological processes contribute to liver function (Hoehme et al 2017;Friebel et al 2015;Drasdo et al 2014a, b;Schliess et al 2014;Vartak et al 2016). Such techniques allow the in silico analysis of which degree of loss of tissue causes loss of function (or metabolic capacity) under the assumption of a proportional relationship.…”
mentioning
confidence: 99%